Urinary Tract Infection in Pediatric Patients on Clean Intermittent Catheterization via a Mitrofanoff port with Reused Catheters – Any Association with Catheter Sterility? - Sam, Cenita James (J Indian Assoc Pediatr Surg, 2020)
OBJECTIVE: The objective of this study is to find out whether the reused catheters for clean intermittent catheterization (CIC) are colonized before insertion and its association with urinary tract infection (UTI). MATERIALS AND METHODS: This is a study conducted on 28 pediatric surgery patients who are on CIC via a Mitrofanoff port and who were reusing catheters, in a tertiary care private medical college hospital for 6-month period. Catheters to be used for the next catheterization were sent for culture along with urine culture. A questionnaire was utilized to assess CIC practice and UTI. RESULTS: Diseases of patients were: neurogenic bladder and exstrophy–epispadias and posterior urethral valve. Twenty-one of them had an augmented bladder. Hydronephrosis was present in ten and vesicoureteral reflux (VUR) in five. Their mean duration of CIC was 5.3 years. Of 28 catheter tip samples, 16 catheters were colonized with organism. Of the 28 urine culture samples, 17 cultures were positive and all were asymptomatic except one. Of the 16 positive catheter samples, only 9 had positive urine culture; four of them had grown different organisms and five of them had the same organism, and even in these five, single organism was seen only in three. Urine culture grew Gram-negative organism in 85%, but catheter grew Gram-positive organism in 46%. No difference was found in the variables between both groups such as hydronephrosis, VUR, and augmented bladder. CONCLUSION: Reused catheters were colonized in 57% of the study patients, but reused catheter may not be the cause of culture positivity or UTI in the study population.